PENGARUH KONSENTRASI ASAM KLORIDA (HCl) DAN WAKTU EKSTRAKSI PADA KARAKTERISASI PEKTIN KULIT JERUK BALI (Citrus maxima) - Zahro, Nur Alfiatus; Warkoyo, Warkoyo; Wahyudi, Vritta Amroini (Universitas Muhammadiyah Malang, 2023)
Pectin or pectate compounds are complex polysaccharides with large molecular weights found in the middle lamella or intercellular spaces in higher plant tissues. The main function of pectin is as a thickener and gelling agent. So far, pectin production in Indonesia has not been widely known and developed. Pectin can be obtained from fruit peels, one of which is grapefruit peel. Grapefruit has a fairly high pectin content, around 30%. The purpose of this study was to find out how much pectin content is in grapefruit peels by determining the concentration of hydrochloric acid and the right extraction time to get the best yield and quality of pectin. This study used a randomized block design (RBD) method with two factors, namely the concentration of hydrochloric acid 0.2 N; 0.25 N and 0.3 N and extraction times of 60, 90 and 120 minutes with three repetitions. The observations made were yield pectin, water content, ash content, equivalent weight, methoxyl content, galacturonic acid and degree of esterification. The data obtained based on the research results were analyzed statistically with variance (α = 0.05) and continued with the Duncan Multiple Range Test (DMRT). The results showed that the concentration of hydrochloric acid 0.3 N and extraction time of 120 minutes produced the best pectin with yield 13.57%, moisture content 8.27%, ash content 7.53%, methoxyl content 6.79%, galacturonic content 261 .65%, the degree of esterification is 14.82% and it can be concluded that the test results for the characteristics of the pectin produced meet the established standards of the International Pectin Producers Association (IPPA).